2021
DOI: 10.3389/fgene.2021.661417
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Satellite DNAs in Genome Architecture and Sex Chromosome Evolution in Crambidae Moths

Abstract: Tandem repeats are important parts of eukaryotic genomes being crucial e.g., for centromere and telomere function and chromatin modulation. In Lepidoptera, knowledge of tandem repeats is very limited despite the growing number of sequenced genomes. Here we introduce seven new satellite DNAs (satDNAs), which more than doubles the number of currently known lepidopteran satDNAs. The satDNAs were identified in genomes of three species of Crambidae moths, namely Ostrinia nubilalis, Cydalima perspectalis, and Diatra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 103 publications
(182 reference statements)
1
23
0
Order By: Relevance
“…Besides their well-known structural function composing heterochromatin, centromeres or telomeres, a relevant role in chromosomal organization, pairing and segregation has been attributed to satDNA [ 8 , 29 ]. For instance, Cabral-de-Mello et al [ 30 ] have recently reported its involvement in the differentiation of the Z sex chromosome in Crambidae moths. Furthermore, non-coding transcripts of satDNA are involved not only in heterochromatin maintenance and kinetochore assembly [ 31 , 32 ], but also in mosquito embryonic development, promoting gene silencing [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides their well-known structural function composing heterochromatin, centromeres or telomeres, a relevant role in chromosomal organization, pairing and segregation has been attributed to satDNA [ 8 , 29 ]. For instance, Cabral-de-Mello et al [ 30 ] have recently reported its involvement in the differentiation of the Z sex chromosome in Crambidae moths. Furthermore, non-coding transcripts of satDNA are involved not only in heterochromatin maintenance and kinetochore assembly [ 31 , 32 ], but also in mosquito embryonic development, promoting gene silencing [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of the most abundant satDNAs in M. elongatus demonstrates not only their intimate evolution with the highly differentiated heteromorphic W 1 sex chromosome, but also confirms that not only general molecular satDNA evolution is at play; particular characteristics of the species also concomitantly generate diversified satellitomes (Ugarković and Plohl, 2002;Lorite et al, 2004, Lorite et al, 2017Richard et al, 2008;Palacios-Gimenez et al, 2017;Cabral-de-Mello et al, 2021). The ZWbased multiple sex chromosome system in M. elongatus shares a conserved heteromorphic W chromosome with the remaining Megaleporinus; but as seen by the two most prevalent satDNAs in the species their interspecific differences show distinct paces for W/W 1 differentiation.…”
Section: Discussionmentioning
confidence: 57%
“…Dalíková et al, 2017b;Cabral-de-Mello et al, 2021). Yet, it seems that abundance of satellite DNA in lepidopteran genomes is very low with scattered distribution and possible enrichment on sex chromosomes (Cabral-de-Mello et al, 2021). This does not reflect distribution of rDNA in Lepidoptera (Nguyen et al, 2010;Provazníková et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Yet we argue that preferential spread of rDNA into terminal regions of lepidopteran chromosomes (Nguyen et al, 2010; Provazníková et al, 2021) favours ectopic recombination as its efficiency depends on proximity of homologous sequences to telomeres (Goldman and Lichten, 1996; Nguyen et al, 2010), whereas ecc-rDNA could be integrated anywhere in the genome as long as a homologous sequence is present. Little is known about satellite DNA in Lepidoptera, which has been studied in detail only in a dozen of species (Lu et al, 1994; Mandrioli et al, 2003; Mahendran et al, 2006; Věchtová et al, 2016; M. Dalíková et al, 2017b; Cabral-de-Mello et al, 2021). Yet, it seems that abundance of satellite DNA in lepidopteran genomes is very low with scattered distribution and possible enrichment on sex chromosomes (Cabral-de-Mello et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation